GNOME 3 Application Development Beginner's Guide - Anwari, Mohammad (Birmingham : Packt Pub., 2013)
This book is a step-by-step guide with ready-to-run codes to guide you in developing applications with GNOME. If you have programming skill either in Linux or other operating systems and want to have GNOME 3 as one of your deployment targets, then this book is for you. This book is also for commercial software developers or an open source software hacker. The reader needs to be familiar with Vala and JavaScript before starting to develop Gtk+ and Clutter applications.
Have a go hero -- trying more JavaScript code hereTime for action -- running our program with Seed; What just happened?; Loosely typed language; Time for action -- playing with data types; What just happened?; Pop quiz -- what is the value now?; Controlling iteration; Time for action -- controlling Iteration; What just happened?; Have a go hero -- counting down; Time for action -- manipulating an array; What just happened?; Have a go hero -- fill with anything you want; Object-oriented programming (OOP) with JavaScript; Time for action -- using the JavaScript object; What just happened?
With great power comes great responsibility.
Description based on print version record.
Keywords: Application software -- Development; Computer programming; Computer software -- Development; Graphical user interfaces (Computer systems); Application software -- Development; COMPUTERS / Programming / Object Oriented; COMPUTERS / Programming / Open Source; COMPUTERS / Software Development & Engineering / General; COMPUTERS / Software Development & Engineering / Tools; Electronic books